Effects of Parameters Variation in Fuzzy based Induction Motor Drives - Marizan Sulaiman; Zulhisyam Salleh; Rosli Omar (Institute of Advanced Engineering and Science, 2015)
This paper presents the effects of parameters variation over the speed response of vector controlled induction motor drives for high performance applications. The design and simulation of fuzzy logic controller are considered based on design case constant parameter fuzzy logic (DCCPFL) controller. The scaling factors for DCCPFL controller are calculated based on identified motor parameter. The performance of the DCCPFL is compared with conventional PI controller. Three different parameters is tested under no-load and loaded conditions namely rotor resistance, inertia and self-inductance. From the simulation results, it is proved that the DCCPFL have better performance in term of different parameter variations and also load disturbances. Thus the DCCPFL is appropriate to replace the conventional PI for high performance of induction motor drives system.